2015
DOI: 10.1080/10509674.2015.1023483
|View full text |Cite
|
Sign up to set email alerts
|

Motivation Among Exoffenders Exiting Treatment: The Role of Abstinence Self-Efficacy

Abstract: The relationships between motivation, treatment readiness, and abstinence self-efficacy were examined among a sample of ex-offenders exiting inpatient treatment for substance use disorders. Hierarchical linear regression was conducted to examine changes in participants’ motivation levels in relation to abstinence self-efficacy beyond what would be expected from treatment readiness and substance use. Abstinence self-efficacy predicted significant decreases in motivation whereas treatment readiness and substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…26-28). In another recent article, Majer, Olson, Komer, and Jason (2015) found that self-efficacy was positively related to motivation for change in ex-offenders. Given that there are well-established psychological instruments that measure these variables, they may provide scope for testing convergent and discriminant validity.…”
Section: Discussionmentioning
confidence: 95%
“…26-28). In another recent article, Majer, Olson, Komer, and Jason (2015) found that self-efficacy was positively related to motivation for change in ex-offenders. Given that there are well-established psychological instruments that measure these variables, they may provide scope for testing convergent and discriminant validity.…”
Section: Discussionmentioning
confidence: 95%
“…We called Factor 1 'Agency' because it loaded on items about personal effort and control as well as items on possibility of change and there is support for this construct in the recent literature (de Vries Robbé et al, 2015;Majer et al, 2015). We called Factor 2 'Optimism' because it included items on the achievability of reintegration and on a sense of being able to belong to society as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…However, in drug treatment research, an area in which knowledge is currently lacking is the association between drug addicts’ motivation when entering drug treatment in relation to their level of self-efficacy. Moreover, existing research in this area has tended to focus on abstinence self-efficacy ( Kelly and Greene, 2014 ; Majer et al, 2015 ) rather than to explore the role of general self-efficacy which covers the overall beliefs in drug addict’s ability to succeed in treatment.…”
Section: Introductionmentioning
confidence: 99%